2013
DOI: 10.1166/jon.2013.1066
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Cationic Gemini and Monomeric Surfactants: Micellar and Surface Properties

Abstract: Attraction effects in the mixed micelle of gemini (C 16 -12-C 16 , 2Br -) and monomeric surfactants i.e. cetyltrimethylammonium bromide (CTAB), cetyltriphenylphosphonium bromide (CTPB) and cetyltributylphosphonium bromide (CTBuPB) mixtures in aqueous solution were investigated by conductivity and surface tension measurements. The attractive interaction of surfactants in the mixed micelle leading to non-ideality has theoretically treated by Clint's and Rubingh's model in the light of regular solution theory. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…The CMC values obtained from the conductivity method are in good agreement with the surface tension and fluorescence methods. The experimental CMC values are in close agreement with published literature data [24,28,[37][38][39][40]54]. It is observed that an increase in the amount of EG and DEG increases the degree of ionization for all the studied surfactants.…”
Section: Cetyldimethylethanolammonium Bromide (Cdmeab)supporting
confidence: 90%
See 1 more Smart Citation
“…The CMC values obtained from the conductivity method are in good agreement with the surface tension and fluorescence methods. The experimental CMC values are in close agreement with published literature data [24,28,[37][38][39][40]54]. It is observed that an increase in the amount of EG and DEG increases the degree of ionization for all the studied surfactants.…”
Section: Cetyldimethylethanolammonium Bromide (Cdmeab)supporting
confidence: 90%
“…This may be due to the reduced [34], b Ref. [40] hydrophobic character of the solution near the interface in the presence of a co-solute facilitating the accumulation of surfactant monomer at the air-liquid interface and hence the observed decrease in surface excess concentration [17,53].…”
Section: Interfacial Propertiesmentioning
confidence: 99%
“…Surfactants with lower CMC values possess greater solubilizing efficiency [27]. We have already reported the CMC of investigated gemini and monomeric cationic surfactants in aqueous solution in Table 2 [27,44,45].…”
Section: Micellar Solubilizationmentioning
confidence: 99%
“…Gemini or dimeric surfactants are twin molecules of monomeric surfactants chemically linked at the hydrophilic head group by a spacer [1][2][3][4][5][6]. Any innovation in preparation of gemini surfactants has been considered important because of their huge acceptability in the numerous industrial applications viz.…”
Section: Introductionmentioning
confidence: 99%